Cross-continental collaboration for understanding postpartum major depression with psychotic features - Kimmel, Mary; Thippeswamy, Harish; Kamperman, Astrid; Madhuri, H. N.; Putnam, Karen; Schiller, Crystal; Weinel, Katie; Rackers, Hannah; Gilden, Janneke; Bergink, Veerle; Meltzer-Brody, Samantha; Chandra, Prabha (Frontiers in Global Women's Health, 2022)
Purpose: Assess postpartum depression and psychotic symptoms from three continents. Methods: Compare numbers of women with depression and psychotic symptoms, mania with or without psychotic features, or transient non-affective psychosis and medication choice. Results: The prevalence of postpartum depression and psychosis and treatment choice differed at each site. Conclusions: Best treatment for postpartum depression with psychotic features has not been established yet. Cross-continental collaboration with similar assessments holds promise to develop best practices for these high risk mother-infant dyads.